Polysaccharide-Based Nanoemulsions for Enhanced Curcumin Delivery: A Multifunctional Strategy for Improving Solubility, Bioavailability and Therapeutic Efficacy - Thangavelu, L.; Gupta, Gaurav; Goyal, Kavita; Rekha, A.; Rana, Mohit; Fuloria, N.K. (Asian Journal of Chemistry, 2025)
Curcumin, a polyphenolic compound derived from turmeric, holds significant promise for therapeutic applications due to its potent anti-inflammatory, antioxidant and anticancer properties. However, its clinical utility is hindered by poor aqueous solubility, low bioavailability and rapid degradation under physiological conditions. In this review, we explore polysaccharide-stabilized nanoemulsions as a versatile drug delivery platform for overcoming these limitations. Natural polysaccharides such as chitosan, pectin, alginate, starch, cellulose derivatives, hyaluronic acid and dextran offer unique functional properties, including mucoadhesion, biocompatibility and stabilization of nanoemulsion systems. These polysaccharide-based carriers enhance curcumin’s solubility, stability and targeted delivery, improving its bioaccessibility and therapeutic potential in various applications such as cancer therapy, wound healing and gastrointestinal disease management. This article provides a comprehensive overview of formulation strategies, physico-chemical considerations and recent in vitro and in vivo findings that support the use of polysaccharide nanoemulsions as effective carriers for curcumin. The findings underscore the promise of these systems in developing advanced pharmaceutical formulations for enhanced therapeutic outcomes.